Pengaruh Kompetensi dan Fasilitas Kerja terhadap Kinerja Pegawai melalui Keterlibatan Kerja pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bungo - Hermanto Hermanto; Fakhrul Rozi Yamali; Mufidah Mufidah (Universitas Batanghari Jambi, 2026)
This study aims to examine the effect of competence and work facilities on employee engagement and their implications for employee performance at the Population and Civil Registration Office of Bungo Regency. The study employed a quantitative explanatory research design. Data were collected through questionnaires distributed to employees and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that competence and work facilities have a positive effect on employee engagement. Furthermore, competence, work facilities, and employee engagement positively influence employee performance. Employee engagement also acts as a mediating variable in the relationship between competence and work facilities and employee performance. These findings suggest that improving employee competence supported by adequate work facilities can strengthen employee engagement, which ultimately enhances employee performance. This study contributes to the development of human resource management literature in the public sector and provides practical recommendations for improving the quality of public services through competency development, adequate work facilities, and stronger employee engagement.